2021
DOI: 10.1111/epi.16931
|View full text |Cite
|
Sign up to set email alerts
|

CSNK2B: A broad spectrum of neurodevelopmental disability and epilepsy severity

Abstract: CSNK2B has recently been implicated as a disease gene for neurodevelopmental disability (NDD) and epilepsy. Information about developmental outcomes has been limited by the young age and short follow-up for many of the previously reported cases, and further delineation of the spectrum of associated phenotypes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 19 publications
4
45
2
1
Order By: Relevance
“…Our cohort reported nine patients with different CSNK2B mutations. Age at onset did not differ from the data presented in the literature (median: 10 vs. 5.5 months; pvalue: 0.09) [1,3,6,[14][15][16]. Interestingly, all our patients displayed epilepsy, with generalized tonic-clonic seizure being the most common phenotype (67%), in agreement with previous studies [1,3,6,[14][15][16].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our cohort reported nine patients with different CSNK2B mutations. Age at onset did not differ from the data presented in the literature (median: 10 vs. 5.5 months; pvalue: 0.09) [1,3,6,[14][15][16]. Interestingly, all our patients displayed epilepsy, with generalized tonic-clonic seizure being the most common phenotype (67%), in agreement with previous studies [1,3,6,[14][15][16].…”
Section: Discussionsupporting
confidence: 89%
“…Our results confirmed such findings, with five (55%) patients presenting facial dysmorphism, as shown in Figure 2. Abnormalities of cranial size have also been described by Ernst et al, who reported two patients with microcephaly and four patients with macrocephaly [3]. In our cohort, 33% of cases presented microcephaly.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Epilepsy in POBINDS is also characterized by unaltered EEG and MRI. Being drug resistant, tonic–clonic seizures are the most frequent presentation [ 2 , 7 , 8 ]. The absence of a specific imaging pattern corroborated in both of our cases to a delayed diagnosis, as exemplified in Case #1 where sleep myoclonus was one of the differential diagnosis owing to the unaltered EEG.…”
Section: Discussionmentioning
confidence: 99%
“…Two de novo missense mutations (p.Asp32Asn and p.Asp32His) in the same CSNK2B codon, which is mutated in patient #2, have recently been associated with CDS [ 3 , 7 ]. Due to the modification of the CK2 structure, the closest CK2 catalytic subunit would be position 32, which could exert a more severe dysmorphic phenotype.…”
Section: Discussionmentioning
confidence: 99%